Effects of various final irrigants on the shear bond strength of resin-based sealer to dentin - Kandaswamy, Deivanayagam (Medknow Publications, 2011)
AIM: This study has been designed to evaluate the effect of strong (MTAD) or soft (1- hydroxyethylidene – 1, 1-bisphosphonate (HEBP) final irrigating solution on the shear bond strength of AH plus sealer to coronal dentin. 17% EDTA was used as the reference. MATERIALS AND METHODS: Forty freshly extracted human maxillary first premolars were prepared using different irrigation protocols (n=10). All the test groups had 1.3% NaOCl as initial rinse and followed by specific final rinse for each group: G1 – distilled water(control), G2 – 17% EDTA, G3- 18% HEBP and G4 – MTAD. Sections of polyethylene tubes that are 3mm long were filled with freshly mixed sealer and placed on the dentin surfaces. The bonding between the sealer and dentine surface was evaluated using shear bond testing. The values were statistically evaluated using one-way ANOVA followed by Tukey's test. RESULT: Significant difference was found among the irrigating regimes. EDTA showed highest bond strength followed by HEBP and MTAD